2020
DOI: 10.3390/foods9101443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interaction between Mealworm Protein and Myofibrillar Protein on the Rheological Properties and Thermal Stability of the Prepared Emulsion Systems

Abstract: In this study, we investigated the effect of replacing myofibrillar protein (pork ham) with edible insect proteins (Tenebrio molitor L.) in meat emulsion systems and examined the interaction between the two types of proteins. We also evaluated the rheological properties and thermal stability of these meat emulsions. The replacement ratios of myofibrillar protein and edible insect protein were as follows: 100:0 (EI0), 80:20 (EI20), 60:40 (EI40), 40:60 (EI60), 20:80 (EI80), and 0:100 (EI100). The pH, redness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 37 publications
8
19
0
Order By: Relevance
“…These results show that the grasshopper flour contributes to color; these findings could consider this ingredient as a pigment. Insect flour can modify color parameters by obtaining darker sausages, usually the edible insect protein is brown or dark in color, which can be attributed to melanin pigments [ 38 ]. The results are in accordance with other authors who incorporated grasshopper Sphenarium purpurascens [ 10 ], cricket Acheta domesticus [ 18 , 37 ], yellow worm Tenebrio molitor L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show that the grasshopper flour contributes to color; these findings could consider this ingredient as a pigment. Insect flour can modify color parameters by obtaining darker sausages, usually the edible insect protein is brown or dark in color, which can be attributed to melanin pigments [ 38 ]. The results are in accordance with other authors who incorporated grasshopper Sphenarium purpurascens [ 10 ], cricket Acheta domesticus [ 18 , 37 ], yellow worm Tenebrio molitor L .…”
Section: Discussionmentioning
confidence: 99%
“…The results are in accordance with other authors who incorporated grasshopper Sphenarium purpurascens [ 10 ], cricket Acheta domesticus [ 18 , 37 ], yellow worm Tenebrio molitor L . [ 36 , 38 , 39 ] and silkworms ( Bombyx mori ) [ 35 , 36 ] to food products as snacks, paté or meat batter, all the case obtained products darker than the control.…”
Section: Discussionmentioning
confidence: 99%
“…The colour values obtained in the a* parameters may be due to the roasting of the SP for consumption, which may promote Maillard reactions due to the presence of amino acids, sugars and proteins causing darkening of the grasshoppers ( Kinyuru et al, 2009 ). Another factor, which may enhance red and yellow tones in insect extracts, is the oxidation of pigments such as melanin and primarily pheomelanin ( Kim et al, 2020 ; Urbina et al., 2021 ). The results of pH and colour coincide to those reported by other authors who incorporated insect protein extracts such as T. molitor larvae or silkworm B. mori pupae in cooked emulsified products ( Park et al, 2017 ; Kim et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The myofibrillar protein gels containing edible insects had a higher pH than that of the control gels (P<0.05). Kim et al (2020) reported that the pH of emulsion systems replacing myofibrillar protein with T. molitor is significantly higher because of the high pH of T. molitor components. Similarly, the results in our study were found to be affected by the myofibrillar protein extraction buffer solution, and it is thought to be affected by the pH of the edible insects.…”
Section: Results and Discussion Ph Colour And Water-holding Capacitymentioning
confidence: 99%